Joint Reconfiguration of Feeders and Allocation of Capacitor Banks in Distribution Systems Using a Multi-Start Strategy - Montsutsumi, Marcio M. [UNESP] (2017)
This paper presents a multi-start optimization algorithm that performs the simultaneous reconfiguration of feeders and allocation of capacitor banks in radial distribution systems. The objective is to find an optimal operating topology for the system together with an optimal plan of investment and operation for capacitor banks that minimizes the operating and investment costs over a chosen horizon. Thus, the cost of energy losses and the investment cost of purchasing and installing capacitor banks should be minimized. In this way, the reconfigured system with the fixed and switchable capacitor banks allocated allows the system to operate efficiently. The effectiveness of the proposed method is demonstrated using the 84-node system, well-known in the specialized literature.